(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The paper contains a synopsis of rare component of flora of Halych National Nature Park forest ecosystems, as well as evaluation of distribution trends of rare vascular plant species and the state of their populations. Being established in 2004, the Park is located in Halych district of Ivano-Frankivsk region on the area of 14684.8 ha. Forests occupy the biggest part of its territory (81.1 %), among which predominate poor and mixed oak (Querceta roboris), beech (Fageta sylvaticae) and hornbeam (Carpineta betuli) woods. Inventory check of plant cover of the forest ecosystems has been done between 2008-2019 years. According to the results of our study, within the forests and forest margins grow 303 vascular plant species, out of which 63 are rare (20.8 %). The list of rare species is composed of species included to the Red Data Book of Ukraine, of species protected by international conventions and directives and complemented by species that are threatened within the study region. Species were considered as threatened if the number of localities and / or population size were small. Regionally rare species were selected based on the analyzes of results of our field survey and materials of herbarium collections. We have found that the third part of rare species (33.3 %) has high coenotic amplitude and a bit less species (26.2 %) favor forest margins. Rare species having low coenotic amplitude are confined to beech woods (19.1 %). Rare species are considerably distinguished by occurrence. Species with scarce occurrence predominate. For instance, 61 % of the species were found in 1-5 localities, of which 25 species occur only in one or two sites. Share of species growing in 6-10 localities within the Park is equal to 26.6 %. Only a small percentage (6.2 %) of rare species comprises species with relatively frequent occurrence (11–20 localities as well as more than 20 cites). Rare species of the Park forests with the highest occurrence rate are Lilium martagon and some members of Orchidaceae family. Predominantly, rare species have populations of small size, for instance, 81.2 % of the species were found in quantities of a few plants – several hundreds of individuals. The most threatened are species general number of which at the Park area is several plants (15.6 %). These species are as follows: Circaea alpina, Atropa bella-donna, Campanula latifolia, Phyteuma spicatum, Epipactis atrorubens etc. The biggest groups comprise species with general number of few tens and several hundreds of individuals (totally 65.6 %). Species with big populations represent far smaller part of forest rare species. Nine rare species grow in the number of several thousands of plants within the Park and three species (Allium ursinum, Galanthus nivalis and Leucojum vernum) – over a million. It has been established that 52.4 % of rare species populations taken together remain in critically bad state, 28.6 % of the populations – in bad state, 14.3 % – in satisfactory state. Only 4.8 % of populations are in good state. Our results show that about 95 % of species are in need of protection and continuous monitoring of population number. Furthermore, 51 species of rare plants, having low number and bad state of populations, require to work out and implement management plans for their restoration.